2017
DOI: 10.1186/s12906-017-1802-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of crude extracts of some South African medicinal plants against multidrug resistant etiological agents of diarrhoea

Abstract: BackgroundThis study evaluated the antibacterial activity of some plants used in folklore medicine to treat diarrhoea in the Eastern Cape Province, South Africa.MethodsThe acetone extracts of Acacia mearnsii De Wild., Aloe arborescens Mill., A. striata Haw., Cyathula uncinulata (Schrad.) Schinz, Eucomis autumnalis (Mill.) Chitt., E. comosa (Houtt.) Wehrh., Hermbstaedtia odorata (Burch. ex Moq.) T.Cooke, Hydnora africana Thunb, Hypoxis latifolia Wight, Pelargonium sidoides DC, Psidium guajava L and Schizocarphu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 45 publications
5
26
0
2
Order By: Relevance
“…Multidrug resistance has become a serious problem in the world, an urgent need for research into novel antibacterial agent and the development of efficacious combinations against multidrug-resistant bacterial clinical isolates are becoming more and more important(Oliveira et al, 2017; Bisi-Johnson, Obi, Samuel, Eloff & Okoh, 2017). Plant extracts used in combination with the antibiotic can be water extract, extracts of different solvents in different parts of plant or a serum containing plant extracts (Ahmad & Aqil, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidrug resistance has become a serious problem in the world, an urgent need for research into novel antibacterial agent and the development of efficacious combinations against multidrug-resistant bacterial clinical isolates are becoming more and more important(Oliveira et al, 2017; Bisi-Johnson, Obi, Samuel, Eloff & Okoh, 2017). Plant extracts used in combination with the antibiotic can be water extract, extracts of different solvents in different parts of plant or a serum containing plant extracts (Ahmad & Aqil, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the target of antibiotics is single, but bacterial mutation is happening more and more, it is difficult to avoid the resistance mutations in bacteria(Schwarz, Kehrenberg & Walsh, 2001). One of TCM antibacterial characteristics is antibacterial ingredients are varied(Xiong, Li, Wang, Hong, Tang & Luo, 2013), which can inhibit or kill bacteria in different ways at the same time(Khan et al, 2015), so the choice of TCM combined with antibiotics can not only effect for a longer time, have a broad spectrum of antibacterial effect(Bisi-Johnson, Obi, Samuel, Eloff & Okoh, 2017d; Rajakumar, Gomathi, Thiruvengadam, Devi, Kalpana & Chung, 2017; Teanpaisan, Kawsud, Pahumunto & Puripattanavong, 2017), but also can be used as inhibitors of multidrug resistance associated protein targets, promoting antibiotics play a better role, reducing the dosage of antibiotics, further reducing the possibility of bacterial resistance to antibiotics, and providing certain clinical medication safety the security(Eumkeb, Tanphonkrang, Sirichaiwetchakoon, Hengpratom & Naknarong, 2017; Eumkeb, Siriwong & Thumanu, 2012; Eumkeb, Siriwong, Phitaktim, Rojtinnakorn & Sakdarat, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of TFCB was determined by serial dilution microplate method (Bisi-Johnson et al, 2017). The tested concentrations of TFCB were from 0.5 µg/mL to 50 µg/mL.…”
Section: Minimum Inhibitory Concentration (Mic) Determinationmentioning
confidence: 99%
“…Bisi-Johnson found that African Aloe vera and some other medicinal plants had appropriate antibacterial activity against multidrug resistant Salmonella typhi , S. enterica serotype Isangi, and other isolates as etiological agents of diarrhea. The isolates were sensitive to crude acetone extracts of African Aloe vera with MIC ranging 0.018 to 2.5 mg/mL [ 33 ].…”
Section: Discussionmentioning
confidence: 99%